Personalized medicine for allergy treatment: Allergen immunotherapy still a unique and unmatched model. Issue 4 (19th October 2020) - Incorvaia, Cristoforo; Al‐Ahmad, Mona; Ansotegui, Ignacio J.; Arasi, Stefania; Bachert, Claus; Bos, Catherine; Bousquet, Jean; Bozek, Andrzéj; Caimmi, Davide; Calderón, Moises A.; Casale, Thomas; Custovic, Adnan; et al.
Abstract: The introduction of personalized medicine (PM) has been a milestone in the history of medical therapy, because it has revolutionized the previous approach of treating the disease with that of treating the patient. It is known today that diseases can occur in different genetic variants, making specific treatments of proven efficacy necessary for a given endotype. Allergic diseases are particularly suitable for PM, because they meet the therapeutic success requirements, including a known molecular mechanism of the disease, a diagnostic tool for such disease, and a treatment blocking the mechanism. The stakes of PM in allergic patients are molecular diagnostics, to detect specific IgE to single‐allergen molecules and to distinguish the causative molecules from those merely cross‐reactive, pursuit of patient's treatable traits addressing genetic, phenotypic, and psychosocial features, and omics, such as proteomics, epi‐genomics, metabolomics, and breathomics, to forecast patient's responsiveness to therapies, to detect biomarker and mediators, and to verify the disease control. This new approach has already improved the precision of allergy diagnosis and is likely to significantly increase, through the higher performance achieved with the personalized treatment, the effectiveness of allergen immunotherapy by enhancing its already known and unique characteristics of treatment that acts on the causes.